2005
DOI: 10.1111/j.1365-2966.2005.09086.x
|View full text |Cite
|
Sign up to set email alerts
|

A new population of extended, luminous star clusters in the halo of M31

Abstract: We present three new clusters discovered in the halo of M31 which, although having globular-like colours and luminosities,have an unusually large half-light radii, ~30 pc. They lie at projected galactocentric distances of approx. 15 to 35 kpc. These objects begin to fill the gap in parameter space between globular clusters and dwarf spheroidals, and are unlike any clusters found in the Milky Way, or elsewhere to date. Basic photometric and derived King profile fit parameters are given, and we discuss possible … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
221
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(229 citation statements)
references
References 39 publications
8
221
0
Order By: Relevance
“…It is worth recalling that Mackey et al (2006) and Mackey et al (2007) noted a strong second parameter effect among the recently discovered group of remote (and/or extended) clusters of M 31 (Huxor et al 2004(Huxor et al , 2005Galleti et al 2006). However, a quantitative and systematic comparison with MW clusters is attempted here for the first time.…”
Section: An Obvious Selection Biasmentioning
confidence: 99%
“…It is worth recalling that Mackey et al (2006) and Mackey et al (2007) noted a strong second parameter effect among the recently discovered group of remote (and/or extended) clusters of M 31 (Huxor et al 2004(Huxor et al , 2005Galleti et al 2006). However, a quantitative and systematic comparison with MW clusters is attempted here for the first time.…”
Section: An Obvious Selection Biasmentioning
confidence: 99%
“…Huxor et al (2005) found three ECs around M 31, which have very large radii above 30 pc. These clusters were detected by chance as the automatic detection algorithms of the MegaCam Survey discarded such extended objects as likely background contaminations.…”
Section: Introductionmentioning
confidence: 99%
“…In general, typical CMDs of M 31 GCs obtained by HST data barely reach the base of the red giant branch (RGB), including most horizontal branch (HB) stars, except the bluest/faintest ones, when present (Ajhar et al 1996;Rich et al 1996;Fusi Pecci et al 1996;Holland et al 1997;Jablonka et al 2000;Meylan et al 2001;Rich et al 2005;Perina et al 2009b;Huxor et al 2004Huxor et al , 2005Huxor et al , 2008Galleti et al 2006;Mackey et al 2006Mackey et al , 2007. In this magnitude range the HB morphology can be used as a rough age indicator, because the presence of RR Lyrae variables and/or blue HB stars implies low-mass progenitors, hence old ages.…”
Section: Introductionmentioning
confidence: 99%